STRATEGI PENGEMBANGAN KEMAMPUAN SARJANA BIDANG AGROBISNIS DALAM MENGAHADAPI DUNIA KERJA - UMI BAROKAH; WIWIT RAHAYU; SETYOWATI SETYOWATI (Universitas Sebelas Maret, 2008)
This research purposedto know the strategy of ability development for agrobusiness to face the word of employment. The basic method which used in this research is a descriptive method. the respondent of this research consist of the alumnus of JPROSEPA UNS (27 respondents) and the users (2 govermental insttutions and 3 private institutions)